Escrita digital no Ensino Fundamental I: do livro didático à sequência didática - Nascimento, Claudia Rodrigues da Silva (2015)
The teaching of writing needs a transformation to assign meaning and interaction within a digital context. The use of technology in schools presents challenges, especially in the early grades. This work is part of the line of research Reading, Writing and Portuguese Language Teaching and it consists to consider the challenges faced in schools, especially those related to writing. The goal is to analyze how writing activities in the digital environment are proposed in Portuguese Textbooks specifically of the 5th year of elementary school and think over the role of schools about the growing demand in this field and their responsibility to prepare the student for what is to come. We depart from linguistic assumptions in their socio-cognitive aspects and sociolinguistics, the contributions of studies of textual linguistics, digital literacy and hypertext. We concluded that textbooks alone are not self-sufficient, they are only instruments. Their use must be planned and linked to other resources, among them, the main one is the intervention of a teacher who does not retreat before challenging didactic situations, but who focus on the thought about the language and put in use the technological resources